Aplikasi Metode Biologi Molekuler pada Model Embrio Ikan Zebra (Danio rerio) dalam Pengembangan Obat Kardiovaskular - Fibe Yulinda Cesa; Martanty Aditya; Devilke Yandriyani; Reflinda Sindy Puspita; Rizal Bing Garumal Indianta (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Cardiovascular diseases remain a leading cause of global mortality and morbidity for 6.9 million deaths in 2021 due to conditions like stroke and ischemic heart disease. The high cost of long-term treatment often leads to decreased medication adherence, spurring the development of new, more affordable yet effective drugs. To minimize risk, animal models are crucial in drug development before human trials. Therapy for cardiovascular diseases continues to evolve due to high costs and poor adherence. Zebrafish have emerged as a promising animal model due to their genetic similarity to humans, allowing for the testing of more efficient and affordable novel drugs. This study reviewed articles on cardiovascular disease in zebrafish embryos from MDPI, PubMed, Science Direct, and Springer Link databases, using specific keywords. Inclusion criteria included quantitative research articles in English or Indonesian, open-access, and published between 2015-2025. Following the PRISMA process (identification, screening, eligibility), 14 relevant journals were selected from 5.680 initial articles and subsequently analyzed using JBI Critical Appraisal Tools for further discussion. The findings indicate that various molecular techniques, such as immunostaining, PCR, and western blotting, enable cardiovascular disease research in zebrafish embryos. This model offers speed, accuracy, and cost-efficiency due to its transparent and replicable nature. Despite requiring specialized skills due to their small size, zebrafish embryos present a promising alternative for developing new cardiovascular drugs.